INFLUENCE OF HERBICIDES ON MORPHO-PHYSIOLOGICAL GROWTH PARAMETERS IN BRINJAL (SOLANUM MELONGENA L.) - B. B.CHNNAPPAGOUDAR,; S. S. MANE,; Y. B. NAGANAGOUDAR,; RATHOD, SANTOSHA (The Bioscan, 2013)
A field experiment was conducted during summer season of 2009 to study the physiological aspects on weed control efficiency (WCE) in brinjal (Solanum melongena L.) at University of Agricultural Sciences, Dharwad. The experiment was laid out in randomized block design with ten treatments consisted of four herbicide treatments at two different concentrations with weed free check and unweeded control and replicated at three times. The morpho-physiological characters and total dry matter accumulation were found to be lowest in unweeded control and application of pendimethalin @ 1.5kg e.i. ha-1 increased all these parameters. The growth parameters viz., leaf area, LAI, AGR, CGR, NAR, LAD, SLW and BMD were significantly lower in unweeded control while the application of herbicides increased these parameters.